Comparison between conservative treatment and plate fixation for displaced middle third clavicle fracture: clinical outcomes and complications - Micheloni, Gian Mario; Tarallo, Luigi; Porcellini, Giuseppe; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2019)
Background: Clavicle fractures are common injuries in adults, especially due to sport activities or road traffic accidents. Most lesions occur at the level of the middle-third presenting some degree of displacement often. Traditionally, non-surgical management was considered the first treatment option for the most clavicle fractures. Nowadays, various authors suggest early surgical fixation of displaced midshaft fractures. The aim of this study is to compare surgical versus non-surgical treatment and to evaluate the outcomes and the incidence of complications following to both treatment options. Matherial and methods: 87 patients with 2 displaced clavicle fractures fragments (AO 15.2A) were included in the retrospective study, evaluating the clinical and functional outcomes and the complication rate with a follow-up average of 48 months. Results: The risk of nonunion resulted lower in the surgically treated patients. The Constant Score after 1 year was slightly better after the plate fixation (94,36 vs 91,36), while the DASH score resulted better in the conservatively treated patients (3,86 vs 4,63). The delay or revision surgery rates were similar for both groups and most of the complications were associated with the conservative treatment. Conclusions: According to our results, the plate fixation does not lead to better clinical and functional outcomes, instead it reduces the risk of nonunion. We suggest to tailor the treatment patient-by-patient considering the functional demand, patient’s comorbidity and nonunion risk factor.